(untitled) (TAJ: Journal of Teachers Association, 2011)
Congenital hypothyroidism with precocious puberty is a rare condition. In this report a rare case of congenital hypothyroidism with precocious puberty is described. A 10 years old girl presented with feature of hypothyroidism together with breast development, vaginal bleeding, lack of pubic hair and delayed bone age. She also had multicystic ovaries. She was treated with L-thyroxine and improved TAJ 2011; 24(1): 48-50